2009
DOI: 10.1016/s1472-6483(10)60165-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of thyroid-stimulating hormone with insulin resistance and androgen parameters in women with PCOS

Abstract: There is a relationship between thyroid function and insulin sensitivity and alterations in lipids and metabolic parameters. Little information is available regarding this relationship in women with polycystic ovary syndrome. However all those pathologies are also described as often affecting women with polycystic ovary syndrome. The association between thyroid-stimulating hormone <2.5 mIU/l and > or =2.5 mIU/l with insulin resistance and endocrine parameters in 103 women with polycystic ovary syndrome was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 48 publications
3
30
1
3
Order By: Relevance
“…None of them reported significant differences (22,25,27,33). Finally, among the four studies that reported outcomes related to SHBG levels, only Dittrich reported that they were significantly reduced in the study group (33.65 ± 17.21 vs 43.55 ± 18.20 nmol/L, P = 0.01) (27,28,29,32).…”
Section: Hormonal Profilementioning
confidence: 90%
See 1 more Smart Citation
“…None of them reported significant differences (22,25,27,33). Finally, among the four studies that reported outcomes related to SHBG levels, only Dittrich reported that they were significantly reduced in the study group (33.65 ± 17.21 vs 43.55 ± 18.20 nmol/L, P = 0.01) (27,28,29,32).…”
Section: Hormonal Profilementioning
confidence: 90%
“…Twelve studies were finally included in the present review, which enrolled 2654 PCOS patients (22,23,24,25,26,27,28,29,30,31,32,33). Among them, 577 women had PCOS and SCH and the remaining 2077 had PCOS only.…”
Section: Included Studiesmentioning
confidence: 99%
“…Only in 2, among 6 studies, total T levels were significantly higher in SCH-PCOS patients [4,35]. Increased T levels were also found in patients with SCH who had only PCOS morphology on ultrasonography [6]. In non-PCOS women, overt hypothyroidism status has been associated with low T levels [3], but the presence of anti-thyroid antibodies seems not to influence T concentrations [29].…”
Section: Discussionmentioning
confidence: 99%
“…Most subjects with subclinical hypothyroidism (SCH) have few symptoms of thyroid dysfunction, but it can lead to clinical, endocrine, or metabolic changes such as dyslipidemia, dysglycemia, insulin resistance, infertility, ovulatory dysfunction, obesity, and abnormal menstrual cycle [3,[6][7][8]. High levels of T, fT, LH, PRL, fasting and postprandial insulin, and glycated hemoglobin (HbA1C), increased homeostasis model assessment of insulin resistance index (HOMA-IR), and decreased levels of SHBG may be present in SCH [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…16 Dittrich R et al have reported altered insulin resistance indices with higher fasting insulin concentration in women with PCOS and with TSH ≥2.5 mIU/l. 17 This increased severity of insulin resistance as well as obesity could have adverse metabolic consequences in hypothyroid PCOS women.…”
mentioning
confidence: 99%